Penerapan Finger Painting dalam Mengembangkan Aspek Perkembangan Motorik Halus Anak Kelas A di Taman Kanak Islam Terpadu Ya Bunayya Sambas - Sera Yuliantini; Reni Arsih (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
The application of Finger Painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas is a study that reveals clear information about: 1). How is the implementation of finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas, 2). The results of implementing finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas 3). Supporting factors inhibiting the implementation of finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas. This study uses a qualitative approach to the type of phenomenological research. Data collection techniques using observation, interviews, and documentation. While the data analysis techniques consist of data reduction, data display, data verification and conclusions. The data sources are educators, principals and students. The research results show that; 1. Implementation of finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas is carried out by prior preparation by making RPPH (daily learning implementation plan), providing tools and materials in the form of paper, finger painting dough, coloring, tissues, 2. The results of the implementation of finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas show that fine motor development is developing very well (BSB) as evidenced by the child's fingers becoming more flexible in coloring using colored pencils and being able to make pattern in the picture, 3. Factors supporting finger painting to develop fine motor development in class A children at TKIT Ya Bunayya Sambas namely good motivation and enthusiasm for children, good environment from family and school, attention and stimulus that supports children's fine motor development , there are sufficient facilities for an children and good nutrition and health for children and the inhibiting factor is the lack of enthusiasm or mood of some students due to illness.